Character Education in Hadith Perspective - Asnidar; Afdal; Surni Kadir (Universitas Muhammadiyah Palu, 2022)
Our current education is very worrying. Problem after problem occurs today in the world of education, both from the educators and the students themselves. The problem of teachers who sometimes commit indecent behavior towards students sometimes cannot be separated from the discussion, as well as students who do inappropriate actions by students. How many cases occur that are committed by students such as drugs, sex free, and we can't free brawls from current problems, sometimes people always blame it on education, so education is a central means of fostering students who become society later. In this increasingly global era, the demand for quality and broad-minded human resources is not only in science but also must be based on good morals so that they can control themselves from the all-permissible cultural influences that accompany the development of science and technology. In education, there is such a thing as Islamic education. This Islamic education that we hope can shape the character of students. Students with these characteristics will give birth to a better generation of the nation and lead to progress.